THE CURRENT IMPORTANCE OF FINANCIAL MANAGEMENT IN THE DIGITAL ECONOMY OF UZBEKISTAN - Salimova Malika Rashidbekovna; Ilyasova Munisa Mirvalievna (Academia Science Repository, 2023)
This article discusses the relevance and importance of financial management in the digital economy today.